Exploring students’ perspectives on misalignment in English summative assessment practices - Ristha Sukmalasari; Fadila Oktaviana; Yayu Heryatun (Journal of English Language Teaching and Learning (JETLE), 2026)
This qualitative case study explores students’ perspectives on the misalignment between English summative assessments and classroom instruction in an Islamic senior high school (Madrasah Aliyah) EFL context in Indonesia. Data were collected from ten students and one teacher through semi-structured interviews, followed by document analysis. Thematic analysis revealed that students consistently perceived a gap between classroom instruction and tested competencies. Document analysis confirmed that several skills assessed in the exam were not adequately covered during instruction. Students reported confusion, anxiety, perceived unfairness, and declining motivation when facing unfamiliar test items. These experiences also reduced self-confidence and academic engagement in English learning. In response, students used coping strategies such as guessing answers and relying on peers, while teachers attempted limited instructional adjustments despite restricted control over test design. The study concludes that assessment misalignment affects both test validity and students’ emotional and behavioral engagement, highlighting the need for stronger alignment and increased teacher involvement in assessment design.